Distinct conformations of the protein complex p97-Ufd1-Npl4 revealed by electron cryomicroscopy. - Bebeacua,C; Förster,A; McKeown,C; Meyer,HH; Zhang,X; Freemont,PS (Proc Natl Acad Sci U S A, 2012)
p97 is a key regulator of numerous cellular pathways and associates with ubiquitin-binding adaptors to remodel ubiquitin-modified substrate proteins. How adaptor binding to p97 is coordinated and how adaptors contribute to substrate remodeling is unclear. Here we present the 3D electron cryomicroscopy reconstructions of the major Ufd1-Npl4 adaptor in complex with p97. Our reconstructions show that p97-Ufd1-Npl4 is highly dynamic and that Ufd1-Npl4 assumes distinct positions relative to the p97 ring upon addition of nucleotide. Our results suggest a model for substrate remodeling by p97 and also explains how p97-Ufd1-Npl4 could form other complexes in a hierarchical model of p97-cofactor assembly.